2015
DOI: 10.1007/s00247-015-3431-8
|View full text |Cite
|
Sign up to set email alerts
|

MR enterography under the age of 10 years: a single institutional experience

Abstract: Diagnostic-quality MRE can be performed successfully in young children. The majority of MRE exams were performed under GA, with only occasional minor side effects/adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Last, 20 patients were given the oral contrast agent through a fluoroscopically placed nasojejunal tube during sedation. Although no major adverse events occurred in the present study, and Sadigh et al (31,32) reported that fluid instillation via nasojejunal intubation with a patient under general anesthesia is a safe technique, the risk of aspiration cannot be ignored. Accordingly, further research is needed to determine whether conventional abdominal MRI is a safer alternative for the diagnosis of MD in younger children.…”
Section: Discussionmentioning
confidence: 48%
“…Last, 20 patients were given the oral contrast agent through a fluoroscopically placed nasojejunal tube during sedation. Although no major adverse events occurred in the present study, and Sadigh et al (31,32) reported that fluid instillation via nasojejunal intubation with a patient under general anesthesia is a safe technique, the risk of aspiration cannot be ignored. Accordingly, further research is needed to determine whether conventional abdominal MRI is a safer alternative for the diagnosis of MD in younger children.…”
Section: Discussionmentioning
confidence: 48%
“…The procedure may be performed in an awake state as in a cooperative older child or using general anesthesia(GA) in younger children. Mollard et al showed that in children less than 10 years of age, >90% of MR enterographic examinations were performed under GA. (4) However, this constituted only 20% of the total pediatric MR enterographic examinations performed in their high volume center. (5) Limiting the motion artifacts and breath holding is required to allow certain sequences which are necessary for interpreting the study.…”
Section: Mr Enterographymentioning
confidence: 99%
“…The type of contrast agent and the optimal volume that does not cause adverse effects remain undetermined. For children, 600-1,000 mL volume depending on age [ 19 ] or 20 mL per kilogram of body weight (maximal dose, 1,350 mL) is generally considered optimal [ 19 20 21 22 23 24 ]. Ingestion of the contrast material over regular intervals facilitates consistent bowel distension.…”
Section: Magnetic Resonance Enterography Techniquementioning
confidence: 99%